Risk of Global Developmental Delay in Infants Born from Mothers with COVID-19: A Cross-Sectional Study - Silva PYF; Lima da Cruz MC; Guerra Azevedo I; Moreira RS; Sousa KG; Pereira SA (Dove Medical Press, 2023)
Pedro Ykaro Fialho Silva,1 Maria Clara Lima da Cruz,1 Ingrid Guerra Azevedo,2 Rafaela Silva Moreira,3 Klayton Galante Sousa,4 Silvana Alves Pereira1 1Physical Therapy Department, Universidade Federal do Rio Grande do Norte, Natal, Rio Grande do Norte, Brazil; 2Dirección de Investigación, Universidad Católica de Temuco, Temuco, La Araucania, Chile; 3Physical Therapy Department, Universidade Federal de Santa Catarina, Araranguá, Santa Catarina, Brazil; 4Physical Therapy Department, Faculdade de Ciências da Saúde do Trairí, Universidade Federal do Rio Grande do Norte, Santa Cruz, Rio Grande do Norte, BrazilCorrespondence: Silvana Alves Pereira, Universidade Federal do Rio Grande do Norte, Physical Therapy Department, Campus Universitário - Lagoa Nova, Natal, Rio Grande do Norte, 59078-970, Brazil, Tel +55 84 99181 8144, Email silvana.alves@ufrn.edu.brPurpose: To investigate the risk of global developmental delay in infants born from mothers with COVID-19.Patients and Methods: A cross-sectional study was conducted between March and November 2021, with 54 infants of both sexes aged between 1 and 12 months. Twenty-seven infants born from mothers diagnosed with COVID-19 during pregnancy composed the COVID-19 group, whereas infants born from mothers not exposed to COVID-19 composed the control group. Medical records and child health booklets provided neonatal and prenatal data. The Survey of Wellbeing of Young Children screened the risk of global developmental delay during a phone interview or home visit. Chi-squared, Mann-Whitney test, and binary logistic regression were applied.Results: The risk of motor developmental delay was identified in 15 infants (12 in the COVID-19 group), while 36 were at risk of behavioral alteration (22 in the COVID-19 group). The COVID-19 group presented a 6.3-fold risk of motor developmental delay. Motor developmental delay was also significantly associated with socioemotional alterations (odds ratio = 6.4, p = 0.01). Regarding families of infants in the COVID-19 group, 63% of the mothers presented risk of depression, 51.9% risk of substance abuse, 40.7% risk of food insecurity, and 7.4% risk of domestic violence. The inflexibility subscale of the survey was a statistically relevant variable for the socioemotional domain.Conclusion: Infants born from mothers with COVID-19 were at high risk of motor developmental delay and socioemotional alterations. Although, this study fills an important gap in the literature regarding the influence of maternal exposure to COVID-19 on infant development, new studies screening families with infants at risk of developmental delay may significantly impact maternal and child health-related indicators, such as physical health, emotional development and social behavior.Keywords: infant development, COVID-19, infant well-being